Informasi Akuntansi Lingkungan: Apa yang Memotivasi Perusahaan untuk Mengungkapkan? - Friendty Friendty; Anita Anita (Owner : Riset dan Jurnal Akuntansi, 2022)
Over the years, there has been an increase in corporate initiatives in the area of environmental reporting practices. The study is conducted to analyze the factors that influence the disclosure of environmental accounting in companies in Indonesia. The sample in this study are 44 entities listed on the IDX from 2016-2020 which are collected by purposive sampling method. The data analysis technique used is panel data regression which is tested with SPSS and Eviews. The results show that firm size, auditor independence and public ownership do not affect environmental disclosure. Profitability affects environmental disclosure negatively. Leverage, listing period and company reputation positively affect environmental disclosure.